Sistema multiagente para estimação da seção em falta em redes de distribuição no contexto de smart grids - Costa, Guilherme Braga da (2023)
Multi-Agent Systems (MAS) are seen by the electricity sector as one of the main allies to solve the problems faced by distribution utilities. Several published studies on MAS discuss their use on the reconfiguration of the distribution network, but few address the preceding step, which is estimating the faulted section. Utilities are evaluated in some aspects, such as the quality of service and the quality of product offered to consumers. The quality of services provided in-volves assessing interruptions in the supply of electricity through indices evaluated by regula-tory agencies. This thesis proposal aims to show how smart meters in conjunction with MAS can improve the utilities’ reliability and supply indices by detecting and locating the faulty section without any consumer intervention. To achieve this goal, the author considers the use of MAS, in the context of Smart Grid (SG), using smart meters (SM), called agents in this work. The purpose of using SM is to employ devices that are already present in a SG. The proposed methodology was implemented in the Java Agent Development Framework (JADE) language, which is a suitable platform for agent development and execution. To validate the proposed method in terms of power supply continuity, the IEEE 34-Node Test feeder was developed using HYPERSIM, a software developed by OPAL-RT Technologies. The results obtained show that the use of smart meter in conjunction with MAS for distribution networks provides agility, efficiency, and automation for the process of detection and location of the faulted sec-tion, eliminating the need for any type of action by the consumer. The next step for consolidat-ing the proposed methodology would be the agent’s implementation in large systems using a real-time simulator and later the physical implementation in real systems. The author believes that other functions can be implemented in SMs in order to improve quality indices and conse-quently consumer satisfaction.